Recent advances in U-type hexagonal ferrites: Synthesis, characterizations, magnetic and absorption properties - Altaz Sher Muhammad; M. Irfan; Majid Niaz Akhtar; Muhammad Azhar Khan; Saima (Hybrid Advances)
Hexaferrites are in high demand due to their unique properties, such as absorbing harmful electromagnetic radiation, which is a result of the development of wireless technology and electronic and electrical gadgets. In meantime, U-type hexaferrites whose chemical formula is Ba4Me2Fe36O60, one of the least explored hexaferrite types getting attention from researchers, and getting explored as a micro-absorbing material and magnetic material due to their complex crystalline structure and increased intrinsic magneto crystallographic anisotropy for wider range of frequency. Several synthesis methods, such as solid-state, sol-gel, chemical co-precipitation, and high-energy milling, are analyzed in this review study, along with their annealing/sintering temperatures and times, for forming several forms of U-type hexaferrite. Additionally, this review paper's emphasized discussion topics include crystal structure, characterization methods, magnetic, microwave-absorbing, and electromagnetic properties. It looked at how substituting other elements could affect the structural, magnetic, and microwave absorption capabilities of U-type hexaferrite. In order to figure out microwave absorber devices spanning an extensive range of frequencies, most researchers have focused on the magnetic and microwave absorbing capabilities of U-type.